Effects of coaching behaviours on self-confidence level of school badminton players in Singapore - Seet, Wei En (2016)
The purpose of the study is to examine how coaching behaviours affects state self-confidence and performance of school badminton players in competition. The coach plays the most important role in the quality and success of an athlete’s sport experience (Mahmoodreza, Alireza, & Zahra, 2013). However, there is limited research that helps to identify the optimal coaching behaviours that enhances the state self-confidence of school athletes in competition. In this study, a mixed method approach will be used. Firstly, a quantitative design will be adopted using established questionnaires to elicit players’ perceptions of their coaches’ behaviours. Follow-up interviews will be conducted on selected players who have top 5 and bottom 5 scores in terms of self-confidence. Participants were 85 school Badminton players, both male (n=33) and female (n=52) with an average age of 14.34 years. (SD= 0.765) Multiple repeated ANOVA and Pearson’s’ correlation tests were run with the data, revealing the following results. Firstly, a positive coaching behaviour leads to higher state self-confidence in competition. Secondly, the performance outcome of winning has an overall effect of raising self-confidence of badminton players. Similarly, losing the match has an effect of decreasing the self-confidence of players. Third, coaches who demonstrate positive personal rapport and effective goal setting skills increase the self-confidence of the badminton players. Consequently, this study can help institutions that train coaches to develop effective education programmes. With a better understanding on how coaching behaviour affects player’s performances, coaches will be trained to be more competent in their job.